2019
DOI: 10.3390/cancers11111797
|View full text |Cite
|
Sign up to set email alerts
|

G-Quadruplex Binders Induce Immunogenic Cell Death Markers in Aggressive Breast Cancer Cells

Abstract: Background: DNA G-quadruplex (G4) structures represent potential anti-cancer targets. In this study, we compared the effect of two G4-targeting compounds, C066-3108 and the gold standard BRACO-19. Methods: In breast and prostate cancer cells, cytotoxicity induced by both molecules was measured by a sulforhodamine B assay. In breast cancer cells, cycle, apoptosis, the formation of G4 structures, calreticulin and high mobility group box 1 (HMGB1), as well as T cell activation, were analyzed by flow cytometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
5
22
1
Order By: Relevance
“…On the other hand, breast cancer patients with high CD8 + CTL infiltration, which correlated with a higher intratumor expression of CRT, have a better survival [46]. Increasing the ICD of triple-negative breast cancer cells with compounds other than conventional chemotherapeutic drugs [47] has been explored in this resistant cancer type. Our data indicate that specific Pgp inhibitors may be useful for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, breast cancer patients with high CD8 + CTL infiltration, which correlated with a higher intratumor expression of CRT, have a better survival [46]. Increasing the ICD of triple-negative breast cancer cells with compounds other than conventional chemotherapeutic drugs [47] has been explored in this resistant cancer type. Our data indicate that specific Pgp inhibitors may be useful for this purpose.…”
Section: Discussionmentioning
confidence: 99%
“…On cell cycle analysis, AMTAC-17 induced an increase in the sub-G1 peak to 41.48% (p < 0.05), associated with a decrease in the G0/G1 phase to 31.30% (p < 0.05), when compared to a control group (26.16 and 43.98%, respectively) ( Figure 2). Literature have shown that the increase in the sub-G1 peak is indicative of the apoptosis process [14,15]. In addition, previous studies suggested that acridine derivatives could induce cell cycle arrest and apoptosis [16].…”
Section: Biological Evaluationmentioning
confidence: 99%
“…For instance, oleandrin, a cardiac glycoside, can induce ER stress in breast cancer cells and trigger ICD-mediated immune responses via the PERK/elF2α/ATF4/CHOP pathway 18 . In addition, Somma et al found that G-quadruplex binders induced ICD in MDA-MB-231 breast cancer cells, accompanied by T-cell activation 140 . Furthermore, Huang et al indicated that the antioxidant N-acetylcysteine (NAC) enhanced not only the antitumor activity of polyglycolylated arginine deiminase (ADI-PEG20), but also the features of ICD, including HMGB1 and ATP secretion 19 .…”
Section: Hmgb1 Serves a Potential Target Breast Cancer Therapymentioning
confidence: 99%